Training and Introduction to Communicative Learning Techniques and Teaching Media for English Transmigration Village Tutors, Karang Indah Village, Mandastana, Barito Kuala - Dina Rafidiyah; Hafizhatu Nadia (Comment: an International Journal of Community Development, 2018)
Speaking as means to communicate is still hard to master for many learners in non-native countries. This fact makes the teaching of speaking for English teachers become a challenging task too. That was the problem in English Transmigration Village, Mandastana, Barito Kuala Regency. Therefore, the lecturers from English Department, University of Muhammadiyah Banjarmasin conducted a training on communicative language learning techniques and teaching media, so the tutors can use it for their future classes. The training was in five sessions, full of practices. The tutors enjoyed the training and planned to use their knowledge based on their needs.